Cost of opioid intravenous patient-controlled analgesia: results from a hospital database analysis and literature assessment - Palmer P; Ji X; Stephens J (Dove Medical Press, 2014)
Pamela Palmer,1 Xiang Ji,2 Jennifer Stephens21AcelRx Pharmaceuticals, Inc., Redwood City, CA, 2Pharmerit International, Bethesda, MD, USABackground: Intravenous patient-controlled analgesia (PCA) equipment and opioid cost analyses on specific procedures are lacking. This study estimates the intravenous PCA hospital cost for the first 48 postoperative hours for three inpatient surgeries.Methods: Descriptive analyses using the Premier database (2010–2012) of more than 500 US hospitals were conducted on cost (direct acquisition and indirect cost for the hospital, such as overhead, labor, pharmacy services) of intravenous PCA after total knee/hip arthroplasty (TKA/THA) or open abdominal surgery. Weighted average cost of equipment and opioid drug and the literature-based cost of adverse events and complications were aggregated for total costs.Results: Of 11,805,513 patients, 272,443 (2.3%), 139,275 (1.2%), and 195,062 (1.7%) had TKA, THA, and abdominal surgery, respectively, with approximately 20% of orthopedic and 29% of abdominal patients having specific intravenous PCA database cost entries. Morphine (57%) and hydromorphone (44%) were the most frequently used PCA drugs, with a mean cost per 30 cc syringe of $16 (30 mg) and $21 (6 mg), respectively. The mean number of syringes used for morphine and hydromorphone in the first 48 hours were 1.9 and 3.2 (TKA), 2.0 and 4.2 (THA), and 2.5 and 3.9 (abdominal surgery), respectively. Average costs of PCA pump, intravenous tubing set, and drug ranged from $46 to $48, from $20 to $22, and from $33 to $46, respectively. Pump, tubing, and saline required to maintain patency of the intravenous PCA catheter over 48 hours ranged from $9 to $13, from $8 to $9, and from $20 to $22, respectively. Supplemental non-PCA opioid use ranged from $56 for THA to $87 for abdominal surgery. Aggregated mean intravenous PCA equipment and opioid cost per patient were $196 (THA), $204 (TKA), and $243 (abdominal surgery). Total costs, including for adverse events, complications, and intravenous PCA errors, ranged from $647 to $694.Conclusion: Although there is variation between different types of surgery, the hospital cost of intravenous PCA after major surgery is substantial. Novel technology should demonstrate cost-effectiveness in addition to clinical superiority.Keywords: patient-controlled analgesia, intravenous, total knee arthroplasty, total hip arthroplasty, abdominal surgery, cost